Antithrombin III Antigen in Human Platelets - Léon Alhenc-Gelas, M; Aiach, M; Gorenflot, A; Andreux, J P (Thrombosis and Haemostasis, 1985)
Immunoreactive AT III was found in human platelets. AT III antigen was quantified in platelets taken from each of 17 healthy donors by a specific competitive enzyme immunoassay using purified AT III and AT III antibodies. AT III antigen levels in extracts of washed platelets disrupted by freezing and thawing ranged from 32 to 140 ng per 109 platelets with a mean value of 70.3 ± 27.3. When stimulated by arachidonic acid, the platelets released AT III antigen together with immunoreactive fibrinogen. These results show that AT III is present in platelets at a level corresponding to approximately 0.01% of total antithrombin in normal blood, and suggest that platelet AT III, like fibrinogen, is contained in the storage granules.
Keywords: Platelet; Antithrombin III; Enzyme immunoassay; Arachidonic acid